2014
DOI: 10.1007/s13139-014-0275-3
|View full text |Cite
|
Sign up to set email alerts
|

Tenosynovial Giant Cell Tumor of Diffuse Type Mimicking Bony Metastasis Detected on F-18 FDG PET/CT

Abstract: Tenosynovial giant cell tumor of diffuse type (TGCT-D) is a locally aggressive neoplasm that arises in the tendon sheath, bursa, or synovium. It typically involves the appendicular skeleton and rarely involves the axial skeleton. Because there are no specific findings of TGCT-D based on imaging studies or clinical symptoms, TGCT-D can be confused with other primary or metastatic bone tumors. We report findings of TGCT-D involving the T9 vertebra incidentally detected on F-18 FDG PET/CT in a patient with papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
1
3
0
Order By: Relevance
“… Therefore, this disease can be easily mistaken for a malignant neoplasm, for example when FDG-PET is performed for staging, as in the current case. Owing to the routine use of FDG-PET as a staging study, reports of incidental findings of TGCTs mimicking malignant neoplasms are becoming more frequent …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“… Therefore, this disease can be easily mistaken for a malignant neoplasm, for example when FDG-PET is performed for staging, as in the current case. Owing to the routine use of FDG-PET as a staging study, reports of incidental findings of TGCTs mimicking malignant neoplasms are becoming more frequent …”
Section: Discussionsupporting
confidence: 78%
“…Owing to the routine use of FDG-PET as a staging study, reports of incidental findings of TGCTs mimicking malignant neoplasms are becoming more frequent. 6,7 Surgical excision of the pathologic tissue is the standard treatment of TGCT and is usually curative for the localized form. In the diffuse type, multiple and invasive surgical procedures often lead to significant adverse effects and the risk for recurrence is high.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several case reports and small series have shown that tenosynovial giant cell tumor can show increased FDG uptake and may cause false-positive result on FDG PET/CT. [6][7][8][9][10] FDG PET/CT findings of facet joints have been rarely reported before. This case indicates tenosynovial giant cell tumor, although rare, should be included in the differential diagnosis of abnormal facet joint FDG accumulation.…”
mentioning
confidence: 99%
“…The MRI features of diffuse-type tenosynovial giant cell tumor are predominant low signal intensity on T2-weighted images and blooming of low signal intensity on gradient echo images 2. Several case reports and small series have shown that tenosynovial giant cell tumor can show increased FDG uptake and may cause false-positive result on FDG PET/CT [6][7][8][9][10]. FDG PET/CT findings of facet joints have been rarely reported before.…”
mentioning
confidence: 99%